Analisis Spasial dan Biogeofisik dalam Pemilihan Lokasi Kebun Benih: Studi Kasus PT. ITCI Kalimantan Timur - Muamar Kadafin; Imam Syaukani; Akbar Al Imam (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2025)
This study aims to determine the potential location of seed gardens in the HPH area of ​​PT ITCI, East Kalimantan, through spatial data analysis based on Geographic Information Systems (GIS). The main data used is the Digital Elevation Model (DEM) which has been converted from the Triangulated Irregular Network (TIN) form to raster for surface analysis purposes. The analysis process includes slope classification into five classes, area cutting (clip), raster data regrouping (reclassify), conversion to polygon form, and spatial overlay using the buffer and intersect functions. The results of the analysis show that areas with gentle slopes (8–15%) dominate the study area with an area of ​​67,533.45 ha, followed by flat areas (0–8%) covering an area of ​​20,751.28 ha. Buffer analysis was carried out on rivers (150 meters) and roads (1,000 meters) to limit the management area, then continued with intersect operations to combine spatial variables such as the number of trees, level of stand damage, and administrative boundaries. Based on technical criteria, namely the number of trees more than 30 trees per hectare, minimal damage level, slope less than or equal to 15%, and a minimum area of ​​2 hectares, 30 land units were obtained that met the requirements as seed garden locations, with areas varying between 2 and 46 hectares. The three selected locations are the result of the integration of all land suitability parameters spatially.